Exploring nurses’ experiences and challenges in managing diabetic amputations: a qualitative study - Ba-Etilayoo Atinga; Albert Henyo; Christiana Asospae Ayamga; Tulukuu Perekuu; Rosemary Braimah (BMC Nursing)
Abstract Background Amputation resulting from diabetes remains a significant public health challenge in Ghana, often culminating in morbidity and mortality. Nurses are the frontline health workers that often manage these patients. Aim This qualitative study explores nurses’ experiences and challenges in the care and management of patients undergone amputation due to diabetic complications at the Sunyani Teaching Hospital in Ghana. Methods Using a phenomenological approach, semistructured interviews were conducted with nurses working in diabetic and surgical units across the Sunyani Teaching Hospital (STH) between April 2024 and July 2024. Results This study showed that nurses face emotional burdens, resource constraints, patient‒nurse relationships, and coping mechanisms in the bid to care for patient with diabetic related amputation. Conclusion The findings provide invaluable insights into the challenges faced by nurses and suggest strategies for improving care delivery and outcomes for individuals with diabetic amputation. Clinical trial number Not applicable.